THE ROLE OF TEACHERS IN THE FORMATION OF RELIGIOUS CHARACTER TO BECOME A SCHOOL CULTURE IN EARLY CHILDHOOD - Roza Yenita (Universitas Panca Sakti Bekasi, 2023)
Early childhood is a unique individual where at this time the growth and development of children is very rapidly developing and needs stimulus to help future growth and development. This study used a qualitative approach with the type of research using descriptive qualitative methods.data collection techniques using observation with questionnaire and interview guidance The sample in the study was 5 teachers in Soraya Kindergarten. This study aims to obtain data on the application of religious character shaping activities to become a culture in schools in Early Childhood.The results obtained from this study show that teachers are able to improve religious character to become a culture in Early Childhood so that children's religious character greatly increases